Editorial - Pacheco Romero, José (2014)
In recent weeks it has been known about the recurrence disease Ebola virus (EVE), a disease that can cause up to 90% lethality. But was detected for the first time in 1976, it remained localized in cities Sudan, Republic of Congo (Central and West Africa). Five species known to date, some lethal. The natural host of the virus is a fruit bat, being virus transmitted to humans by wild animals and spread from person to person. Produce dismay know that the virus man is acquired by contact with narrow bodies, secretions, semen and other fluids body, as well as by customs bodies in preparation ceremonies and funeral procession. period Incubation ranges from 2 to 21 days. Men can continue to transmit the virus in semen up to seven weeks after clinical recovery (1). The virus is identified by ELISA, antigen detection tests and neutralization, reverse transcriptase PCR (RT-PCR) cell culture. The infection of medical personnel to treat patients with EVE has been common when there has been close contact and have not been observed strictly precautions for infection control.